2007
DOI: 10.1080/00036840600690223
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of immigration: labour market performance and education in the second generation

Abstract: Previous research finds that the children of immigrants, or the second generation, earn at least as much as other native born but that there are persistent ethnic differences in the intergenerational transmission of education and wages. We explain why these results are not incompatible and extend the empirical evidence in several directions using the Canadian Survey of Labour and Income Dynamics. First, we estimate a model of wages, earnings and hours worked using modern econometric techniques to corroborate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In the 2006 Canadian census data, 36% of the children of immigrants held degrees, compared with 24% of the third-and-higher generation. And children with two immigrant parents register a larger positive education gap than those with only one immigrant parent (Hum and Simpson, 2007;Aydemir and Sweetman, 2008). This higher level of achievement is most noticeable among the visible minority 2 nd generation (Boyd, 2002;Aydemir and Sweetman, 2008).…”
Section: A Brief Review Of Educational Outcomes Among the Children Ofmentioning
confidence: 97%
“…In the 2006 Canadian census data, 36% of the children of immigrants held degrees, compared with 24% of the third-and-higher generation. And children with two immigrant parents register a larger positive education gap than those with only one immigrant parent (Hum and Simpson, 2007;Aydemir and Sweetman, 2008). This higher level of achievement is most noticeable among the visible minority 2 nd generation (Boyd, 2002;Aydemir and Sweetman, 2008).…”
Section: A Brief Review Of Educational Outcomes Among the Children Ofmentioning
confidence: 97%
“…We should tell them about the results of 14 Though, it is possible that immigrants arrive knowing they will have difficulties but making the move in the interests of the subsequent generations. Canadian researchers have been at the forefront of the literature on the economic outcomes of the children of immigrants (see, for examples, Finnie and Mueller 2008, Aydemir et al 2013, Aydemir and Sweetman 2008, Hum and Simpson 2007, Worswick 2004and Warman and Worswick 2016. These studies find that immigrant children and immigrants who arrive as children do relatively well in terms of educational attainment but since parental income plays some role in educational outcomes, they could do even better if the problem of poor immigrant earnings could be addressed (Bonikowska and Hou 2010). research showing that if they come from certain countries, they will have difficulty transferring their human capital and that the fact that they pass through a point system does not imply that the Canadian government has given them a stamp of likely success.…”
Section: Responses To Problems With Immigrant Earningsmentioning
confidence: 99%
“…Canadian researchers have been at the forefront of the literature on the economic outcomes of the children of immigrants (see, for examples, Finnie and Mueller , Aydemir et al. , Aydemir and Sweetman , Hum and Simpson , Worswick and Warman and Worswick ). These studies find that immigrant children and immigrants who arrive as children do relatively well in terms of educational attainment but since parental income plays some role in educational outcomes, they could do even better if the problem of poor immigrant earnings could be addressed (Bonikowska and Hou ).…”
mentioning
confidence: 99%
“…The early Canadian research suggested that the most important determinant of the gap was parents" education, as well as age and residential location (Boyd 2002;Hum and Simpson, 2007;Bonikowska, 2008). However, parental education may be a proxy for other effects, such as the aspirations of the parents regarding educational outcomes, educational resources made available to the child, and the valuation of education by the parents or the student.…”
mentioning
confidence: 99%